Optimal bid disclosure in license auctions with downstream interaction - Cuihong Fan; Byoung Heon Jun; Elmar G. Wolfstetter (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2014)
The literature on license auctions for process innovations in oligopoly assumed that the auctioneer reveals the winning bid and stressed that this gives firms an incentive to signal strength through their bids, to the benefit of the innovator. In the present paper we examine whether revealing the winning bid is optimal. We consider three disclosure rules: full, partial, and no disclosure of bids, which correspond to standard auctions. We show that more information disclosure increases the total surplus divided between firms and the innovator as well as social surplus. More disclosure also increases bidders' payoff. However, no disclosure maximizes the innovator's expected revenue.
urn:nbn:de:bvb:19-epub-21109-3
Keywords: D21; D43; D44; D45; 330; Auctions; innovation; licensing; information sharing